The silent and the vocal: Participation and learning in whole-class discussion. (April 2017) - O'Connor, Catherine; Michaels, Sarah; Chapin, Suzanne; Harbaugh, Allen G.
Abstract: We explore vocal vs. silent student participation in whole-class mathematics discussion in relation to learning outcomes, relying on additional data analysis from a previously published in vivo controlled comparison in two sixth grades (n = 44) which contrasted an "academically productive talk" (APT) condition (emphasizing frequent discussion) with a "direct instruction" condition (without discussion), where content was tightly controlled across conditions. In the current study, controlling for a variety of factors, we find no relationship between the degree to which students contributed vocally during the lessons, and those students' scores on the outcome measure, in either condition. This finding adds to a growing literature on participation in classroom discussion, and may inform thinking about the multiple constraints faced by teachers as they attempt to orchestrate whole-class discussions. However, we suggest that this result can most confidently be applied to classrooms in which a culture of active participation has already been established. Highlights: Silent vs. vocal participation is one challenge of orchestrating whole-class discussion. An in vivo study shows that silent and vocal students learn content equally well. A critical component of similar results is a culture of engagement. This result may offer flexibility in the short run for teachers managing discussion. Benefits of vocal participation still require inclusion for all over the long run.